The Effect of Management Practices on Improving The Quality of Services Through The Integrated Core Practice of Efqm and Six Sigma Public Health Center, Jambi Province - Andy Amir; Andi Subandi; Dwi Noerjoedianto (International Journal Of Health Science, 2022)
This study aims to analyze the effect of management practices on improving service quality through the integrated core practice of EFQM and Six Sigma Public Health Centers in Jambi Province. This research is a quantitative research using a cross sectional design approach through two stages of research. The research data was obtained using a questionnaire from a sample of 560 civil servant employees in 24 health centers that were randomly selected and analyzed by second order using Smart-PLS 3.0. The results of the study found that the implementation of management practices and core practices had a fairly good average by employees and each had a direct effect on the service quality of the Public Health Center. The core practice is able to partially mediate between management practices and the quality of Public Health Center services. However, in practice, not all Public Health Center have implemented quality management practices.